2006
DOI: 10.1053/j.gastro.2005.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Novel Agents in the Treatment of Intestinal Failure: Humoral Factors

Abstract: Modalities to care for patients who suffer from intestinal failure comprise 2 basic approaches: supportive care and interventions that promote the normal adaptive process of the gastrointestinal tract. During this adaptation, the gastrointestinal tract and other organs release a number of humoral factors, which are critical to promote increased intestinal growth and function. The 3 lectures, summarized below, discuss 3 of the more well-known factors: human growth hormone, epidermal growth factor, and glucagon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Previous studies by our group have shown that IEL play an important role in the maintenance of the gut barrier function and in the support of intestinal EC growth 6, 7, 11, 13, 31. Several studies have indicated that EC may have an important role in mucosal immune responses by helping to regulate IEL phenotype and function 20, 22.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies by our group have shown that IEL play an important role in the maintenance of the gut barrier function and in the support of intestinal EC growth 6, 7, 11, 13, 31. Several studies have indicated that EC may have an important role in mucosal immune responses by helping to regulate IEL phenotype and function 20, 22.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, also EGFR expression has found to be significantly increased after SBR only in the D-SBR group. EGFR has been shown to be of crucial importance for postresectional intestinal adaptation [31,[42][43][44]. Stimulation of EGFR in vivo was found to result in an enhancement, whereas its' inhibition led to attenuation of post-resectional intestinal adaptation [42].…”
Section: Discussionmentioning
confidence: 99%
“…IEL act as the initial lymphoid defense layer against intraluminal foreign antigens (7), and may be of critical importance for proper functioning of the mucosal immune system (35). Previous studies by our group have shown that IEL play an important role in the maintenance of the gut barrier function and support intestinal EC growth (42)(43)(44)(45)47). There is an average of 10 -20 IEL per 100 villi EC in human small intestine (11).…”
Section: Introductionmentioning
confidence: 99%